Aplicación de las metodologías de observación directa e indirecta en el monitoreo del zorro andino (Lycalopex Culpaeus), para determinar su presencia en los cerros de la parroquia Belisario Quevedo. - Chamorro Pillajo, Lizeth Dayana (2023)
The Andean Fox (Lycalopex Culpaeus) is a solitary animal, what can adapt easily, since being a consumer within the trophic chain, it has a large prey number, becoming an opportunistic animal. It was determined the Andean Fox presence in the Belisario Quevedo parish from Latacunga canton, Cotopaxi province, through the direct and indirect methods application for the mammals monitoring, solving 16 transects distributed in the parish. What corresponds to Cerro Putzalahua, it was observed Andean Fox tracks, which were at significant distances between other, into different extension and widths non-linear trails; for this reason, it was adopted to follow the available trails, tracing 13 transects (TA, TB, TC, ... TL) without distance limit and covering a representative extension from Putzalahua. That is to say, it did not opt for transects with a delimited distance, in order not to lose traces records. On the other hand, in the eastern region from parish, the situation is different. The zone is outside the perimeter from Cerro Putzalahua and corresponds to an area completely intervened by agricultural and livestock activities, where they are used the only feasible accesses of travelling to set 1.5 km distance three transects: in Chaupi Contadero (TM Transect), the via to Palopo (TN Transect) and on the border with Salcedo (TO Transect). It was also sought to verify, if there is a relationship between the samples found (such as rabbit feces, cattle feces, rodent corpses, bone remains, and Lycalopex culpaeus feces), and the inspected land altitude into Belisario Quevedo by using chi square tests. Into conclusion, there is a verified Lycalopex culpaeus presence into said parish, it determines, through traces, which were photographed and geographically positioned, furthermore, it is demonstrated the relationship its occurrence with anthropic activities, regardless of used transects altitude. In short, an Andean Fox population inhabiting the Belisario Quevedo parish can mean a large-scale impact both in the preservation field and in the economy revitalization based on the ecotourism.